Knowledge, Attitude, and Practice of Nurseries’ Workers toward Infection Prevention among the Children - Al-Shatari, Sahar Abdul Hassan; Ghafouri, Tayser Salah (AL-Kindy College Medical Journal, 2021)
Background: Infections are common in the children attending daycare centers how act as predisposes to it. Hygienic interventions have a fundamental role in infection control and disease prevention in child care settings. Objective: - To evaluate the knowledge, attitude, and practice of nurseries workers in infection prevention and control among the children. Subjects and Methods: A cross-sectional study using the researcher-developed questionnaire validated by two experts and piloted and 100 nurseries-workers had participated in it. Result: the mean age of participants was 37.5 years±12.1, (37%) aged 18-30 yrs, 58% married, and 57% with higher education, 54% of nurseries the participant take care of 11-20 children. 67 (67%) had correct knowledge about infection control, (91%) had the corrected practice, but unfortunately, 47 (47%) had low-attitude. Education level has significantly associated with the knowledge, attitude, and practice of the child care workers. Conclusion: the majority of the nurseries workers had good knowledge and correct practice and less about their attitude in infection prevention.